Dampak Covid-19 terhadap Perubahan Harga Saham dan Volume Transaksi (Studi Kasus pada PT Matahari Departement Store, Tbk) - Eny Suheny; Mega Arum; Bayu Pratama Ngiu (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The economic impact of the Coronavirus / COVID-19 crisis on various industries, and countries. It also provides estimates of the potential global economic costs of COVID-19, and GDP growth in various countries. Showing the economic impact of the current outbreak is being underestimated, relying too much on historical comparisons with SARS (severe acute respiratory syndrome), or the 2008/2009 financial crisis. This study aims to determine a significant comparison of stock prices and transaction volumes in the presence of the covid 19 pandemic (case study at PT. Matahari Department Store, Tbk). The data from this study were taken from 42 days before Covid-19 and 42 days after the announcement of the first case of Covid-19 in Indonesia. processing and data analysis using paired sample t-test using SPSS. Based on the results of data analysis, it can be concluded that there was a significant difference in stock prices before and after the announcement of the first Covid-19 case in Indonesia, the significance value was indicated by 0.00 < 0.05, with stock prices experiencing a decrease compared to before the Covid-19 case. as well as the volume of stock transactions, the results of data analysis showed a significant difference with a significance value of 0.00 < 0.05. Then the volume of stock transactions after the announcement of covid-19 showed an increasing value